Responsible government and ministerial responsibility: every reform is its own problem - Sutherland, S.L
The article defends the classical version of ministerial responsibility against recent initiatives to implement a form of direct accoutability for administrators. Constitutional convention and ministerial resignations from active cabinets in the Canadian federal government and in Britain and described in neither country do ministers resign for maladministration by their officials, nor does doctrine suggest they should. Rather, the pattern of resignations indicates the importance of collective responsibility, as well as the relative unimportance of ministerial misbehaviour. The conclusion sets out the negative implications for democratic government of substituting a kind of direct "accountability" of offic
Keywords: Ministerial Responsibility; Government; Canada; Cabinet System; Cabinet System - Canada